Vaccinium myrtillus (Bilberry) Extracts Reduce Angiogenesis In Vitro and In Vivo - Matsunaga, Nozomu (Oxford University Press, 2010)
Vaccinium myrtillus (Bilberry) extracts (VME) were tested for effects on angiogenesis in vitro and in vivo. VME (0.3–30 µg ml(−1)) and GM6001 (0.1–100 µM; a matrix metalloproteinase inhibitor) concentration-dependently inhibited both tube formation and migration of human umbilical vein endothelial cells (HUVECs) induced by vascular endothelial growth factor-A (VEGF-A). In addition, VME inhibited VEGF-A-induced proliferation of HUVECs. VME inhibited VEGF-A-induced phosphorylations of extracellular signal-regulated kinase 1/2 (ERK 1/2) and serine/threonine protein kinase family protein kinase B (Akt), but not that of phospholipase Cγ (PLCγ). In an in vivo assay, intravitreal administration of VME inhibited the formation of neovascular tufts during oxygen-induced retinopathy in mice. Thus, VME inhibited angiogenesis both in vitro and in vivo, presumably by inhibiting the phosphorylations of ERK 1/2 and Akt. These findings indicate that VME may be effective against retinal diseases involving angiogenesis, providing it can reach the retina after its administration. Further investigations will be needed to clarify the major angiogenesis-modulating constituent(s) of VME.